Projective Behaviour of Nur– Quantitative Experimental Research - Renans, Agata Maria (Proceedings of the Amsterdam Colloquium, 2011)
The paper presents the results of the experiment on the projective meaning of nur (German: only). The data from German shows that the prejacent of nur projects easily out of counterfactual if-clauses, whereas its projective behaviour changes when it is embedded in indicative if-clauses. The obtained results classify projection out of counterfactuals as a reliable test for projective meanings in the cross-linguistic perspective, on the one hand, while shedding more light on the semantics of nur and conditionals, on the other.